Diálogos públicos no centro de Belo Horizonte: mapas de sentidos em comunicação urbana - Milene Migliano Gonzaga (2009)
Our work intends to produce meaning maps of communicative situations of the public dialogs in Belo Horizonte downtown. The researchs Urban Cartographies photographies register urban communicative cultural practices, such as inscriptions, pixação, graffiti, stencil, stickers, propaganda, and also the erasing practices on theses texts. The photographic images will be accessed on the production of the public dialog maps, which connect the meaning produced by everyday relations among people downtown and the cultural contexts, intending to compose the urban communicative processes. The communicative situations, which apropriate of spaces and resources available in the city constitute places and ways of urban communication. The text intends to understand symbolic ways, by the communicative situations which are conformed on the citys downtown, using the relations among the communicative practices production and their strategies and tactic ways of operation as a starting point. By mapping the meetings which are established on these communicative processes, we try to turn visible some relations of urban sociability, which are developed among the ocupied territories, and the social temporalities, articulating diferent ways of ones participation on the urban dynamics.